(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Стаття присвячена дослідженню й уточненню поняття правової культури. Проаналізовано види правової культури, розкрито взаємозв’язок культури, правової культури суспільства та особистості. Ключові слова: культура, правова культура, правова культура суспільства, правова культура особистості, правова культура професійної групи, верховенство права. The article is devoted to the legal culture notion research. Types of legal culture are analyzed, the relationship of personality legal culture and society legal culture is revealed. Key words: culture, legal culture, society legal culture, personality legal culture, specialists’ legal culture, rule of law.